2007
DOI: 10.1093/jmedent/41.5.117
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Infection in Mosquitoes in the Mid-South USA, 2002–2005

Abstract: West Nile virus (family Flaviviridae, genus Flavivirus, WNV) was first detected in the Tennessee Valley and in Alabama in August 2001. In summer 2002, intensive viral activity was seen, but in subsequent years, viral activity settled into an enzootic pattern. Here, we report an analysis of viral activity in the mosquito fauna in the Mid-South from 2002 (the first year viral activity was detected in mosquitoes) through 2005. Eight mosquito species were infected with WNV during 2002. However, viral activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…erraticus has been shown to feed upon reptiles at the TNF site. This is the most common species found at the TNF site and throughout the Southeastern United States 21,[28][29][30] and it is believed to represent a major potential vector of EEEV in this region. 21,28 It is therefore possible that any or all of these four mosquito species might be responsible for initiating the enzootic transmission cycle through feeding upon EEEV-infected snakes exiting hibernation in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…erraticus has been shown to feed upon reptiles at the TNF site. This is the most common species found at the TNF site and throughout the Southeastern United States 21,[28][29][30] and it is believed to represent a major potential vector of EEEV in this region. 21,28 It is therefore possible that any or all of these four mosquito species might be responsible for initiating the enzootic transmission cycle through feeding upon EEEV-infected snakes exiting hibernation in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…quadrimaculatus in Memphis, while Cx. salinarius has been implicated as a potential bridge vector in Connecticut (Andreadis et al 2004) and has been found to be frequently infected with WNV in studies conducted in the Southeastern United States (Godsey et al 2001, 2005, Cupp et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that C. pipiens in the eastern United States may feed on mammals and humans instead of birds during the late summer and early fall, and this "host switching" has also been reported with C. tarsalis in the western United States (96,212). There are several reports of WNV in Aedes mosquitoes, though they are not considered a primary vector in nature (46,58,83,184,216,221). WNV has also been detected in field-collected male A. triseriatus and C. salinarius (219), which not only points to vertical transmission of virus, as only females feed on animal blood, but also further supports that WNV has the ability to infect Aedes mosquitoes in nature.…”
Section: Vector Preferencementioning
confidence: 99%